Morphological and Biochemical changes in pollinated flowers of different Aerides species - Deepti, Srivastava; M.C, Gayatri; Sitikantha, Sarangi (Current Botany, 2013)
Aerides, an ornamental orchid, can remain fresh for longer period if left unpollinated. In the present study, unpollinated A. odoratum, A. crispa, A. maculosum and A. ringens flowers were stay fresh for 17 days (d), 15d, 13d and 11d respectively. Their pollinated flowers become senescent at 5 days after pollination (DAP), 4d, 12 Hour after pollination, 4DAP and 3d, 12HAP respectively. Pollinated flowers had higher contents of sugars and free amino acids than unpollinated flowers in all species studied. The amount of sugars and activity of enzymes were relatively greater in the pollinated flowers of A. odoratum followed by A. crispa, A. maculosum and A. ringens, reflecting their faster rate of senescence compared to unpollinated flowers. Among floral organs, column and ovaries had relatively lower level of sugars and enzymes compared to lip and perianth at unpollinated stage, although former tissues showed greater contents of simple molecules in the pollinated flowers. It demonstrates signals related to pollination had up-regulated enzymatic activities and mobilization of simple molecules from the lip and perianth to the column and ovary. An increase in anthrocyanin contents and decrease in carotenoid level were found in wilted pollinated flowers which lead to darkening of lips in all species.